Pengembangan bahan ajar materi statistika menggunakan pendekatan saintifik berbantuan geogebra - Nurcahyati, Yoanda; Putra, Harry Dwi; Anita, Ika Wahyu (IKIP Siliwangi, 2023)
This study aims to determine the feasibility of developing statistics teaching materials using a geogebra-assisted scientific approach. The development research method with 3D models includes the define, design, and develop stages. The research was conducted at SMP Negeri 3 Cimahi, which is located in the Sriwijaya complex in Cimahi City. The research subjects in the small-scale trial were 15 students in class VIII-I, and in the large-scale trial, there were 33 students in class VIII-K. The data collection method used instruments in the form of interview sheets, validation sheets, and student response questionnaires. Data processing techniques used descriptive statistics with the help of the 2019 version of Microsoft Excel software were analyzed to find out the results of the validation and practicality analysis. Based on the results of the data analysis, it shows that the teaching materials developed have the interpretation of